2021
DOI: 10.3390/ma14092397
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Modeling of Thermal Protective and Thermo-Physiological Comfort Performance of Polymeric Textile Materials—A Review

Abstract: In 2017, more than 60,000 firefighters and oilfield-workers injuries and fatalities occurred while they were working under various thermal hazards such as flame, radiant heat, steam, etc., or due to their significant heat stress related discomfort. The majority of these burn injuries and fatalities results from an inadequate protection and comfort provided by firefighters’ and oilfield-workers’ fire protective polymeric textile materials used in their workwear. Hence, both the thermal protective and thermo-phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 80 publications
(179 reference statements)
1
16
0
Order By: Relevance
“…The results of the regression analyses showed that a larger air gap, especially at the level of the abdomen and upper arm, is related to an increase in exposure duration and a decrease in skin temperature change over time at a radiation intensity of 1.5 and 2.0 kW/m 2 . This is in line with the hypothesis of this study, that an increase in air gap thickness is related to an increase in the thermal protective performance of process operators’ clothing and confirms multiple other studies related to the air gap and clothing fit [ 8 , 12 , 14 , 42 , 43 ]. At the radiation intensity of 2.5 kW/m 2 , only the air gap at the upper arm seems to be an indicator of the mean skin temperature change over time of the whole body.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the regression analyses showed that a larger air gap, especially at the level of the abdomen and upper arm, is related to an increase in exposure duration and a decrease in skin temperature change over time at a radiation intensity of 1.5 and 2.0 kW/m 2 . This is in line with the hypothesis of this study, that an increase in air gap thickness is related to an increase in the thermal protective performance of process operators’ clothing and confirms multiple other studies related to the air gap and clothing fit [ 8 , 12 , 14 , 42 , 43 ]. At the radiation intensity of 2.5 kW/m 2 , only the air gap at the upper arm seems to be an indicator of the mean skin temperature change over time of the whole body.…”
Section: Discussionsupporting
confidence: 93%
“…It should be noted that in the close vicinity to a regular flare or an unintentionally ignited cold flare, the radiative heat flux levels are much higher than the values analyzed in the present study. However, inside the industrial site perimeter, the zone closest to such equipment is generally considered a sterile zone with very infrequent work, and the workers are generally equipped with clothing that protects against much higher heat fluxes [36,37]. Thus, exposure to very high heat fluxes that may generate deeper burns, e.g., deep partial-thickness burns [38], is outside the current study, which focused on low heat radiation levels.…”
Section: Skin Damage Modelingmentioning
confidence: 99%
“…Therefore, the loss of tensile strength was considerably lower than dry and single layer moist conditions. The presence of moisture in the thermal liner could increase the heat capacity of the fabrics, which resulted in a significant amount of thermal energy storage within the fabric system [6,59,63,64].…”
Section: Effect Of Moisture and Radiant Heat On Tensile Strength Of O...mentioning
confidence: 99%
“…In total, 48 firefighters died while on duty in the U.S. in 2019 [4]. Improved protective clothing can minimize the risk of injuries to firefighters [5,6].…”
Section: Introductionmentioning
confidence: 99%